The Environmental Dimensions of Iraqi Urban Legislation and Laws they Specialize in Environmental Protection Legislation (Global Journals of Research in Engineering, 2022)
The legislation and laws related to protection against the natural environment aim to achieve a balance between what is taken from the natural environment and what can be achieved to protect it by the contemporary ideas of the international organizations of Earth Day and environmental protection organizations That legislation has directed reflections on the protections against urban and architectural environments that are achieved by activating the role of the institutions under the names of environmental protection to adopt basic legislation for protecting the urban and architectural environment The general problem of research is to determine the shortcomings of the environmental dimensions of Iraqi legislation laws and instructions and the reality of the control system in the light of the renewable mechanisms in this area The research aimed to assess the status of the local legislative system through a practical study to identify the category of specialists that are directly involved in the system The planners engineers and designers The research concluded to identify important indicators in the development and updating of the system of legislation to protect the urban and architectural environment and the regulatory system following the principles of sustainable development and investment of the characteristics of the environment and renewable energy as well as activating the supervisory role and participation of the individuals themselves by raising awareness of the importance of environmental protection
Keywords: environment; legislation; urban; architecture; Iraq